2009
DOI: 10.1111/j.1365-3040.2009.02005.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and physiological responses reveal multi‐phasic acclimation of Arabidopsis thaliana to chronic UV radiation

Abstract: Biochemical changes in vivo and pathway interactions were investigated using integrated physiological and metabolic responses of Arabidopsis thaliana L. to ultraviolet (UV) radiation (280-400 nm) at 9.96 kJ m -2 d -1 over the entire life cycle from seed to seed (8 weeks). Columbia-0 (Col-0) and a UV-B sensitive accession ( fah-1) showed significant (P < 0.001) reductions in leaf growth after 6 weeks. Col-0 recovered growth after 8 weeks, with recovery corresponding to a switch from production of phenylpropanoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 68 publications
3
61
1
Order By: Relevance
“…These findings differ from those of laboratory based studies on seeds where UV-B reduced seed size and numbers (e.g. Lake et al 2009;Singh et al 2010).…”
Section: Seed Germination Responses To Uv-bcontrasting
confidence: 55%
See 1 more Smart Citation
“…These findings differ from those of laboratory based studies on seeds where UV-B reduced seed size and numbers (e.g. Lake et al 2009;Singh et al 2010).…”
Section: Seed Germination Responses To Uv-bcontrasting
confidence: 55%
“…UV-B alone has been studied in the context of seed production and viability (van de Staaij et al 1997;Wang et al 2008;Lake et al 2009) and also as a potential tool to manipulate or beneficially enhance the secondary metabolite chemistry of fruit and vegetables (see review by Jansen et al 2008). For example, research has been conducted on UV-B impacts on grape berries due to commercial interest in fruit characteristics and resultant wine quality.…”
Section: Introductionmentioning
confidence: 99%
“…Abiotically, life in bare microhabitats might require adaptations to increased disturbance (45), rockiness, drought (55), and exposure to high levels of UV light (36). Adaptations like the production of heat-shock proteins and UV-absorbing phenols and flavonoids may have costs that reduce competitive ability (56,57). Likewise, adaptations to disturbance, which are associated with a lack of vegetation cover in serpentine and other bare soils (45,52) and which may perpetuate a lack of vegetation (58), may also have costs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, all studies dealing with high UV stress found an increase in antioxidants, and especially phenolics concentration in various crops (Wang & Frei, 2011). Flavonoids, one of the largest classes of plant phenolic, protect plant cells from UV-B radiation because they accumulate in epidermal layers of leaves and stems and absorb light strongly in the UV-B region while letting visible (PAR) wavelengths throughout uninterrupted (Lake, Field, Davey, Beerling, & Lomax, 2009). In addition, exposure of plants to increased UV-B light has demonstrated to increase the synthesis of flavones and flavonols.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%